THE ROLE OF PROVERBS IN LINGUOCULTURE - Jumayeva Nodirabonu (International Journal of Literature and Language Studies, 2026)
Proverbs are an essential component of every nation’s linguistic and cultural heritage. They preserve collective experience, moral values, traditions, and social norms that have been formed over centuries. In linguoculturology, proverbs are studied as linguistic units reflecting the worldview, mentality, and cultural identity of a particular people. This article examines the role of proverbs in linguoculture and analyzes their functions as carriers of cultural knowledge. The study explores the theoretical foundations of linguoculture, the characteristics of proverbs, and the relationship between language and culture. In addition, the article provides a linguocultural analysis of English and Uzbek proverbs, focusing on cultural values, symbolism, imagery, and national mentality. The comparative analysis demonstrates that although many proverbs express universal human experiences, their figurative meanings and cultural associations differ according to historical, social, and cultural contexts. The research highlights the importance of proverbs in preserving cultural memory and promoting intercultural understanding.